2017
DOI: 10.1536/ihj.17-246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Autophagy on Cardiovascular Senescence and Diseases

Abstract: SummaryThe risk of cardiovascular disease increases with age, causing chronic disability, morbidity, and mortality in the elderly. Cardiovascular aging and disease are characterized by heart failure, cardiac ischemia-reperfusion injury, cardiomyopathy, hypertension, arterial stiffness, and atherosclerosis. As a cell ages, damaged organelles and abnormal proteins accumulate. A system for removing these cytoplasmic substrates is essential for maintaining homeostasis. Autophagy assists tissue homeostasis by formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 106 publications
0
39
0
Order By: Relevance
“…As a physiological process that effectively prevents the accumulation of abnormal proteins and organelles, autophagy is crucial for maintaining cell self‐renewal and energy homeostasis (Sciarretta, Maejima, Zablocki, & Sadoshima, ). Autophagy preserves cardiac structure and function under baseline conditions and is activated during stress (Sasaki, Ikeda, Iwabayashi, Akasaki, & Ohishi, ), limiting damage under most conditions (Sciarretta et al, ). Functional autophagy reduces injury and preserves cardiac function during ischemia (Godar et al, ; Sciarretta, Yee, Shenoy, Nagarajan, & Sadoshima, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a physiological process that effectively prevents the accumulation of abnormal proteins and organelles, autophagy is crucial for maintaining cell self‐renewal and energy homeostasis (Sciarretta, Maejima, Zablocki, & Sadoshima, ). Autophagy preserves cardiac structure and function under baseline conditions and is activated during stress (Sasaki, Ikeda, Iwabayashi, Akasaki, & Ohishi, ), limiting damage under most conditions (Sciarretta et al, ). Functional autophagy reduces injury and preserves cardiac function during ischemia (Godar et al, ; Sciarretta, Yee, Shenoy, Nagarajan, & Sadoshima, ).…”
Section: Discussionmentioning
confidence: 99%
“…12) Autophagy is maintained at low levels under normal conditions, but this process is altered by several pathological or physiological conditions, such as starvation, endoplasmic reticulum stress, oxidative stress, aging, and disease pathogenesis. [13][14][15][16][17] Previous studies reported autophagy levels were inhibited in the ischemic myocardium in both in vitro and in vivo models of heart I/R injury. 18,19) Enhanced autophagic flux functions as a protective countermeasure against I/R injury in cardiac myocytes.…”
mentioning
confidence: 99%
“…Autophagy plays a crucial role in prolonging longevity, and it has been proposed that autophagy is bound up with organ aging (Sasaki et al, 2017) and cell senescence (Levine and Kroemer, 2008). Damaged organelles and abnormal proteins accumulate continuously as cells age, while autophagy maintains tissue homeostasis by degrading these substances.…”
Section: Discussionmentioning
confidence: 99%